2022
DOI: 10.3390/bios12090718
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evaluation and Nephrotoxicity Assessment of Human Renal Proximal Tubule Cells on a Chip

Abstract: An in vitro human renal proximal tubule model that represents the proper transporter expression and pronounced epithelial polarization is necessary for the accurate prediction of nephrotoxicity. Here, we constructed a high-throughput human renal proximal tubule model based on an integrated biomimetic array chip (iBAC). Primary human renal proximal tubule epithelial cells (hRPTECs) cultured on this microfluidic platform were able to form a tighter barrier, better transporter function and more sensitive nephroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…These results confirm the influence of fluid shear stress on renal proximal tubule secretion. These data are consistent with reports of increased OAT1 and other transportermediated absorption efficiency in fluidic models of the renal proximal tubule, including both membrane-based (Jing et al, 2022) and tubule-based (Sakolish et al, 2023). Our observations suggest that the augmented secretion of pAH under fluidic conditions is likely due to heightened activity in influx (OAT1) and efflux (MRP) pathways, as pAH secretion involves both basolateral uptake through OAT1 and apical release through MRP2, the latter also known to be affected by shear stress (Vriend et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…These results confirm the influence of fluid shear stress on renal proximal tubule secretion. These data are consistent with reports of increased OAT1 and other transportermediated absorption efficiency in fluidic models of the renal proximal tubule, including both membrane-based (Jing et al, 2022) and tubule-based (Sakolish et al, 2023). Our observations suggest that the augmented secretion of pAH under fluidic conditions is likely due to heightened activity in influx (OAT1) and efflux (MRP) pathways, as pAH secretion involves both basolateral uptake through OAT1 and apical release through MRP2, the latter also known to be affected by shear stress (Vriend et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Out of the 20 various cell types in the human kidney, the renal proximal tubule epithelial cell is the major target of renal damage due to its specific roles. Cisplatin is absorbed and accumulated in proximal tubular cells and triggers oxidative stress, inflammation, vascular injury, cell apoptosis, necrosis, and endoplasmic reticulum stress and impaired expression of different transporters ( Jing et al, 2022 ). Cisplatin induced proximal tubular injury leads to decreased sodium reabsorption and hyponatremia.…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that gentamicin mediated tubule damage by a 3.2-fold increase in glucose uptake, reversing the circulation flux of the tricarboxylic acid cycle, leading a 40-fold enhance in lipid accumulation, and demonstrated the SGLT2 inhibitor empagliflozin inhibited gentamicin toxicity by 10-fold. Jing B et al designed a proximal tubule model using an integrated biomimetic array chip to compare the characteristics of several chemotherapeutic drugs ( Jing et al, 2022 ). The chip comprised 24 functional units, each consisting of five layers.…”
Section: Functional Kidney Units-on-a-chipmentioning
confidence: 99%
“…Substances in blood and urine were exchanged through the porous membrane, simulating the reabsorption and secretion processes of PTECs Disease model: renal lithiasis (Wei et al, 2012), renal interstitial fibrosis (Zhou et al, 2014), Lowe syndrome (Naik et al, 2021); drug nephrotoxicity test: cisplatin (Jang et al, 2013;Vormann et al, 2021), tenofovir (Vormann et al, 2021), tobramycin (Vormann et al, 2021), cyclosporine A (Vormann et al, 2021), gentamicin (Ioannidis et al, 2022), polymyxin B (Jing et al, 2022), adriamycin (Jing et al, 2022) and sunitinib (Jing et al, 2022); transporter study: P-glycoprotein (Vriend et al, 2018), MRP2/4 (Vriend et al, 2018), OCT2 (Nieskens et al, 2020) PTECs polarization and drug transporter expression are limited (Qu et al, 2018;Zhang and Mahler, 2023),adriamycin (Qu et al, 2018;Zhang and Mahler, 2023) 1) Challenges in vascularization.…”
Section: Gecs and Podocytesmentioning
confidence: 99%